Opposition Text Structure - Kim, Tatyana S. (International Journal of Psychosocial Rehabilitation, 2020)
In analyzing the essays of Korean authors, it should be noted that in these works antonymy functions as one of the types of semantic-syntactic organization of the text, it, like contrast, according to G.V. Andreeva, can have a non-systematic character and enter the compositional structure of the text in the form of separate fragments of the meaning of the opposite, and can be a principle for constructing the text itself, can also concentrate on a specific section of the text as a combination of stylistic techniques. This fact reveals the applicability of the hypothesis E.A. Miller about the presence of a “largeantonymy” not only in any literary text, but also in the text of the essay. At the present stage, Korean scholars such as Ko Yong Geun, Kim Pong Sung, And Sam Hyun and others dealt with the problems of the text. In Kim Pong Sung’s research on the principles of text construction, we find that one of the types of text connectivity is matching relationships (Pak Yong Sung explains that matching relationships in this case include comparison or contrast). The positive relations, expressed in the essays by Bobchon and Han Yong Un and others, characterize the specific character of the text and the personality of the author. For understanding the manifestation of antonymy, it is necessary to take into account the national mentality, culture of the people, their way of life, traditions, religion inherent in Korean society.